2019
DOI: 10.4239/wjd.v10.i5.311
|View full text |Cite
|
Sign up to set email alerts
|

Association between sarcopenic obesity and higher risk of type 2 diabetes in adults: A systematic review and meta-analysis

Abstract: BACKGROUND The coexistence of sarcopenia and obesity is referred to as sarcopenic obesity (SO) and it has been hypothesized that the two components of SO may synergistically increase their negative effects. However, many uncertainties still surround this condition especially with regard to its potential negative effects on health outcomes. AIM To conduct a systematic review to determine the prevalence of sarcopenia among adults with overweight and obesity and to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 50 publications
0
56
0
3
Order By: Relevance
“…Similarly, Baumgartner et al [83] demonstrated that although T2DM was more frequent in sarcopenic subjects, the prevalence of T2DM was found to be highest in the nonsarcopenic obese group, followed by that of the sarcopenic obese group, and the lowest being in the sarcopenic nonobese group. Conversely, a recent systematic review and meta-analysis of 11 studies showed that sarcopenic obesity increased the risk of T2DM by 38% when compared with sarcopenia or obesity alone [108]. However, these results need to be interpreted with caution as the cross-sectional design of the studies reviewed indicated simple associations between sarcopenic obesity and T2DM without providing definitive information regarding causal relationships between the two conditions.…”
Section: Diabetesmentioning
confidence: 97%
“…Similarly, Baumgartner et al [83] demonstrated that although T2DM was more frequent in sarcopenic subjects, the prevalence of T2DM was found to be highest in the nonsarcopenic obese group, followed by that of the sarcopenic obese group, and the lowest being in the sarcopenic nonobese group. Conversely, a recent systematic review and meta-analysis of 11 studies showed that sarcopenic obesity increased the risk of T2DM by 38% when compared with sarcopenia or obesity alone [108]. However, these results need to be interpreted with caution as the cross-sectional design of the studies reviewed indicated simple associations between sarcopenic obesity and T2DM without providing definitive information regarding causal relationships between the two conditions.…”
Section: Diabetesmentioning
confidence: 97%
“…However, sarcopenic non-obese and non-sarcopenic obese participants were not associated with an increased 10-year CVD risk. More recently, a meta-analysis of studies examining the associations between sarcopenia obesity and type 2 diabetes has been performed, with eleven studies including a total of 60 118 adults who were overweight or obese (75) . Sarcopenic obesity was significantly associated with a 38 % increase in risk of type 2 diabetes compared with those without sarcopenic obesity (OR 1•38, 95 % CI 1•27, 1•50), but results should be interpreted with caution as the majority of studies were cross-sectional.…”
Section: Various Measurementsmentioning
confidence: 99%
“…Another study showed that patients with SOB have a higher risk of metabolic syndrome, type 2 diabetes, and atherosclerosis [104]. According to a recent systemic review including 11 articles about the prevalence of SOB and the prevalence of diabetes, co-existence of sarcopenia and obesity increases the risk of type 2 diabetes by nearly 38% when compared with those with obesity alone [105]. The five-year study with 1231 men aged over 70 years demonstrated that older men with SOB have increased probability of common metabolic syndrome compared with counterparts with healthy body habitus [106].…”
Section: Association Of Sob With Metabolic Disease and Cardiovascularmentioning
confidence: 99%